El caso de enseñanza en la formación del Pedagogo 1989-0257 - Nono, Maevi Anabel [UNESP] (2013)
This article refers to a research-intervention of qualitative nature in which we sought to evaluate the formative and investigative potentials of the use of teaching cases and the case method in teacher education. During the years of 2006/2008, 44 students analyzed teaching cases that contemplated school situations faced by other teachers, and constructed a teaching case from teaching situations they experienced. Teaching cases, how it was used, allowed access and interference in students' knowledge about the career. Teaching cases have proved themselves to be valuable tools in the process of teacher education.